Not a shirt on my back, not a penny to my name”: an insight on the english language literacy of street adolescents and pedagogical practices of an alternative school - Raslie, Humaira; Jamaluddin, Sharizan (Issues in Language Studies, 2013)
This study examined the presence of dominant literacy and the pedagogical scaffolding in an English Language learning classroom of an alternative school in Malaysia. Focusing on street children, two questions were stipulated to guide the research process: (1) What are the dominant practices vis-à-vis English language literacy present during teaching and learning session? and (2) How does the facilitator provide scaffolding for the students in acquiring the dominant practices of English literacy?. An observation was conducted at the research site and the data gathered was thematically analysed using the operative paradigms of New Literacy Studies and Hegemony. Consequently, it was found that the alternative school’s learning system showed an inclination towards autonomous practices. However, the scaffolding efforts made by the instructor managed to fairly bridge the knowledge gap between the education system and the students. This research therefore advocates that alternative school’s teaching and learning process should remove itself from the autonomous shadow of mainstream schools. In order to provide a holistic and contextualised learning environment for its marginalised clients, there is a pivotal need to acknowledge their unique socio-cultural schemata. This could be accomplished by adding ideological approaches to the existing pedagogical practices.